SPECIFICS OF CORPORATE MANAGEMENT IN AGRIBUSINESS IN TRANSITIONAL CONDITIONS - Vignjević-Djordjević, Nada; Jovićević, Predrag; Kocić, Stefan (Economics of Agriculture, 2015)
Corporate governance in agribusiness describes an agency problem resulting from separation of ownership from control in modern corporations and represents a huge cost to the shareholders. The agency problem is regulated by legal protection of minority shareholders, by constituting the Board of Directors as a Supervisory authority to monitor managers and an active agribusiness market for corporate control in agribusiness (against hostile takeover). These mechanisms are regulated by regulations on securities (at the federal level), corporate law (at the state level), and the corporate statutes, regulations and other Contracting Rules (at the company level). These regulations, laws and decrees actually defne distribution of power between shareholders and managers. Such techniques of defense against takeover can be benefcial to shareholders, if managers use them to strengthen the bargaining power and increase the selling price of an agribusiness company. However, if managers use it for preservation of position and for the achievement of personal interests these regulations do not contribute to the realization of shareholders interests.